Peningkatan Aktivitas Fisik dan Pemanfaatan Pekarangan Rumah untuk Tanaman Sayuran dan Buah sebagai Gerakan Masyarakat Hidup Sehat (Germas) di Desa Penyengat Olak Kecamatan Jambi Luar Kota Kabupaten Muaro Jambi 2020 - Suryani Suryani; Neni Heryani; Indarmien Netty Ariasih (Jurnal Abdimas Kesehatan (JAK), 2021)
According to the World Health Organization (WHO 2013), the prevalence of anemia in the world ranges from 40-88%. The number of pregnant women (10-19 years) in Indonesia is 26.2%, consisting of 50.9% men and 49.1% women (Choiriya, 2015). The prevalence of anemia in pregnant women in Muaro Jambi has been reported by Kalsum and Halim in 2015 were 67% with the main cause being the lack of the habit of having breakfast. Isaati in 2014 also reported the prevalence of anemia among pregnant women in Jambi City, which was 78.7% due to the lack of frequency of eating, consumption of tea, coffee and consumption of iron-enhancing foods. Even though Germas was only launched in 2017, it needs initiation starting from the smallest community groups such as dasa wisma, groups of pregnant women. This Community Service activity will focus on 3 Germas sub-activities, namely increasing physical activity for pregnant women, namely pregnancy exercise. Health checks with tension checks on pregnant women, counseling with the theme of nutritious eating for pregnant women, and utilization of house yards for vegetables and fruit plants. This activity has been carried out through community mobilization, especially for pregnant women in the work area of the Penyengat Olak Health Center, to get involved from planning to evaluation of activities. So that counseling and tension checks can be carried out on October 26, 2020, as many as 20 pregnant women from 4 villages, with pregnancy exercises and ending the distribution of vegetable and fruit crops